CCN: A novel energy efficient greedy routing protocol for green computing. (22nd March 2018) - Siddiqa, Ayesha; Qureshi, Faisal Fayyaz; Shah, Munam Ali; Iqbal, Rahat; Wahid, Abdul; Chang, Victor
Summary: We proposed a novel Energy Efficient Greedy Routing Protocol (EEGRP) in CCN for MANETs to achieve the gaps in the existing infrastructure of Green Cloud Computing. Initially, the consumer node broadcasts the interest packet; each relay node verifies if it is already satisfied, and then it drops the packet. Otherwise, the provider node selects shortest path to unicast data packet within minimum delay. Each relay node receives a data packet, stores its content in content store, and forwards it to next node according to path mention in the hop‐count field. If the data packet custodian node does not find path mention in the hop‐count field, then it searches the routing table entries to choose the second best path to unicast the data packet. EEGRP is implemented in three scenarios using ns2 and compare its performance with AIRDrop routing protocol on bases of three performance parameters like packet delivery ratio, delay, and energy consumption. EEGRP achieves high PDR with minimum delay and less energy consumption as compared to AIRDrop. Therefore, EEGRP is feasible to use on green computing and cloud technology. This can save energy issue to secure energy for Green Computing and Cloud before moving to full‐scale virtualization and Cloud services.